Empirical Study of Moral Obligations, Trust in Government and Intention to Be Compliant toward Tax Compliance - Kantohe, Meidy Santje Selvy; Kambey, Joseph (International Journal of Applied Business and International Management, 2021)
This study aims to investigate the tax compliance behavior of taxpayers' internal factors, particularly the perception of individual taxpayers regarding moral obligations, trust in government and intentions to be compliant. The research was conducted by modifying the TPB model by replacing new predictors that affect intention, moral obligation and trust in the government. The population in this study were all individual taxpayers who were registered at KPP Pratama Manado. Samples with purposive sampling technique are all individual taxpayers registered at KPP Pratama Manado whose taxes are not deducted by third parties or who have independent jobs. The results showed that 1) the higher the morale of the taxpayer, the higher the intention of the taxpayer to be compliant and the higher the level of taxpayer compliance. 2) the higher the level of trust of taxpayers to the government, the taxpayers will behave obediently to taxes. 3) The higher the intention of the taxpayer to be compliant, the more the taxpayer will behave obediently to taxes.